Measuring technological change through patents and innovation surveys - Archibugi, Daniele (Technovation)
This article provides an overview of recent research using innovation surveys and patent data as indicators of technological activity. The conceptual and methodological problems of 'measuring' technology are discussed, with a classification of the types of information which can be drawn from patent databases and from surveys of both innovations and the innovative efforts of firms. The findings and the methodological strengths and weaknesses of such studies are reviewed, considering first the evidence at the firm level, second the analysis of the industrial structure and finally the evidence at the country level and the process of globalization. The overview shows that rich and important evidence on the technological activities of firms is offered by these indicators. A summary of new departures for research based on innovation and patent data concludes the paper.